Happiness in Everyday Life. - Takehisa, Yuu; Tsukasa, Mori (Mito : Contemporary Art Center Art Tower Mito Mito-shi, 2009)
Asai, Yusuke ; Ben-Ner, Guy ; Morita, Hiroaki ; Ohmaki, Shinji ; Miyajima, Tatsuo ; Iwasaki, Takahiro ; Kosuge1-16 ; Hibino, Katsuhiko ; Kamiya, Satoshi ; Ume, Kayo ; Atelier Bow-Wow ; Nishio, Yoshinari ; Fuji, Hiroshi ; Bohr, Marco
biog. tent. p. 83-85
Japans
Engels
Exhibition. Happiness in Everyday Life. Mito-shi. Contemporary Art Center Art Tower Mito Mito-shi, 25.10.2008 - 18.1.2009.
boek